Un silenzio molto profumato - alcune riflessioni sul romanzo „La lunga vita di Marianna Ucrìa " di Dacia Maraini - Kornacka, Barbara (Studia Romanica Posnaniensia, 2007)
The article devoted to novel La lunga vita di Marianna Ucrìa of Dacia Maraini constitutes a reflection upon cognition by means of senses. The analysis concerns the experience of cognition of the world (people, situations, places) by the main character, deaf and dumb person, whose sensual cognition of the reality is dominated by the sense of sight and smell. The analysis concentrates on the character of smelling sensations, indicating their crucial but forgotten function of the contact with the reality and its interpretation. The article highlights the problem of non verbality and non-divisibility of perceptions of the sense of smell, which the author of the novel Dacia Maraini faced.